Analysis of the Effectiveness of Services and Governance of Heavy Equipment Lending at the UPTD Heavy Equipment and Laboratory of West Sumbawa Regency - Yadi, Sahrul; Yamin, Ahmad; Najamuddin, Najamuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to describe the form of heavy equipment lending services and the governance of heavy equipment lending at the UPTD Heavy Equipment and Laboratory of West Sumbawa Regency, as well as analyzing both in depth. This research uses the Mix Method, which combines quantitative and qualitative approaches. The research results show that there is a positive correlation of 0.228 between lending services and lending governance. However, this correlation is not statistically significant at the 95% confidence level, with a significance value of 0.108. Nevertheless, these findings show that improvements in service quality tend to be followed by improvements in lending governance, although this relationship is not yet significant. This research suggests the need to increase synergy between services and lending governance, as well as focus on improving service quality and strengthening more efficient lending governance. Optimizing these two aspects is expected to support improving the overall operational quality of UPTD.